2021
DOI: 10.3390/fermentation8010014
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions among Isolates of Lactiplantibacillus plantarum and Dairy Yeast Contaminants: Towards Biocontrol Applications

Abstract: Yeast diversity in the cheese manufacturing process and in the cheeses themselves includes indispensable species for the production of specific cheeses and undesired species that cause cheese defects and spoilage. The control of yeast contaminants is problematic due to limitations in sanitation methods and chemicals used in the food industry. The utilisation of lactic acid bacteria and their antifungal products is intensively studied. Lactiplantibacillus plantarum is one of the most frequently studied species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Therefore, it remains unclear whether the strain variability in clades can influence the production of antifungal metabolites with target activity, especially when isolates are from similar competitive environments. Our recent study [15] confirmed that strains from microbiologically rich environments, such as silages, have considerable inhibitory effects on a spectrum of yeasts.…”
Section: Bacteriocin Gene Class Iiasupporting
confidence: 68%
See 4 more Smart Citations
“…Therefore, it remains unclear whether the strain variability in clades can influence the production of antifungal metabolites with target activity, especially when isolates are from similar competitive environments. Our recent study [15] confirmed that strains from microbiologically rich environments, such as silages, have considerable inhibitory effects on a spectrum of yeasts.…”
Section: Bacteriocin Gene Class Iiasupporting
confidence: 68%
“…The extracellular proteins and peptides were isolated and visualised as described by [15], with minor changes. The Amicon ProAffinity Concentrator 30.000 NMWL (Merck Millipore Ltd., Tullagreen, Ireland) was used according to the instruction manual to concentrate the extracellular proteins and peptides in the CFS.…”
Section: Chitinase Productionmentioning
confidence: 99%
See 3 more Smart Citations